Hate revisited! - Bagge, Peter (Fantagraphics Books, 2025)
"Legendary cartoonist Peter Bagge triumphantly returns to the series that defined a generation with this all-new Hate graphic novel. Buddy Bradley and Lisa Leavenworth, now middle aged with a free-spirited young adult of their own, confront their own poor decisions as young people in the grungy 1990s. Expertly shifting between the present day (in full color) and their Gen X heyday (in glorious, crosshatched black-and-white), we learn for the first time the story of how Buddy met Lisa, Stinky, George, and Val. Meanwhile, Buddy is forced to come to terms with the tragic -- and covered-up -- circumstances of Stinky's untimely death in the original Hate series, while navigating elder care, contemporary politics, family and friendships. Hate Revisited! expertly showcases Bagge's inimitable humor and knack for character, and the generational shift lends an unexpected gravitas to their lives. While the original Hate is indelibly rooted in a key pop cultural era, the themes and characters of Hate remain timeless. Misanthropy never gets old! Full-color and black-and-white illustrations."--Amazon.com.